Women in Cosmetic Plastic Surgery: An Analysis of Female Authorship in Cosmetic Plastic Surgery Over the Last 10 Years. Issue 3 (September 2021) - Swarnkar, Pari; Sinha, Vikram; Spake, Carole; Crozier, Joseph; Ngaage, Ledibabari M.; Roussel, Lauren O.; Borrelli, Mimi R.
There is a significant gender gap in research conducted by women in plastic surgery. Previous work has not explored female authorship trends in cosmetic plastic surgery. We asked how authorship trends in cosmetic plastic surgery compare with those in plastic surgery overall, over the last 10 years. All the articles published in Journal of Plastic Reconstructive and Aesthetic Surgery (JPRAS), Facial Plastic Surgery and Aesthetic Medicine (JAMA facial plastics), and Aesthetic Surgery Journal . (ASJ) in 2009, 2014, and 2019 were retrieved. The gender of the first and last author was determined. In addition, article type and total number of authors were extracted. Chi-square or Fisher exact test were performed to determine differences between groups Linear regression models were used to investigate whether total number of authors, or female last authorship predicted female first authorship. A total of 4358 articles were reviewed. Of these, 16.6% (n = 723) were published by a female first and/or last author. Percent of female first and/or last author increased with time, from only 12.2% in 2008, to 15.9% in 2014, reaching 21.7% in 2019. A total of 25% (n = 181) of randomized controlled trials were published by a female first and/or last author compared with only 14% (n = 440) of case studies. Female first and last authorship both increased across the 10-year study period, but there were consistently more female first authors than female last authors in all 3 surveyed years ( P < .001). There was an 86% increased chance of female first authorship if the last author was also female ( P < .001), and a 7% increased likelihood of female first authorship ( P = .002). Women have a lower representation in the cosmetic plastic surgery literature than men. This gender disparity gap, however, is decreasing. While encouraging, opportunities for improvement remain.